APLIKASI PEMODELAN DENGAN MENGUNAKAN SOFTWARE BOSS SMS UNTUK KEMAMPUAN KECEPATAN YANG TEREDUKSI AKIBAT RUMPUN BAKAU - Ahmad Refi (JURNAL TEKNIK SIPIL ITP, 2014)
Boss of Sms represent alternative software of so can water down consumer for to assorted model my me of hydrogen in the form of 2D. Constructively sms software 5.0 ability of mangrove reduce speed of stream like result of simulation earn easily in applying field Data able to be read at result of simulation in the form of graph can be explained as follows is. Thickness mangrove forest 250m there are discount speed of stream range from 21% to 71% for the length of mangrove forest 50m and 41% to 79% for the length of mangrove forest 100m.Thickness mangrove forest 500m there are discount speed of stream range from 21% to 78% for the length of forest 50m and 50% to 90% for the length of forest 100m.Ketebalan mangrove forest 750m there are discount speed of stream range from 28% to 87% for the length of forest 50m and 54% to 91% for the length of forest 100m. Thickness mangrove forest 1000m there are discount speed of stream range from 32% to 91% for the length of forest 50m and 56% to 93% for the length of forest 100m.